PENGARUH PEMBERIAN SLUDGE DAN URIN SAPI TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Lubis, Dicky Ferial; Sjofjan, Jurnawaty ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aimed to determine the effect of interaction giving sludge and cow urine to the growth of oil palm seeds (Elaeis guineensis Jacq.) and get a suitable combination for the growth of oil palm seedlings in main nursery. The research was conducted from August to November 2015. The research used to completely randomized design (CRD) factorial consisting of two factors. The first factor is the sludge consists of 4 levels: sludge dose of 0 g/plant, sludge dose of 50 g/plant, sludge dose of 100 g/plant and sludge dose of 150 g/plant. The second factor is the concentration of cow urine consists of 4 levels: cow urine concentrations of 0 %/plant, cow urine concentration of 20 %/plant, cow urine concentration of 40 %/plant and cow urine concentration of 60 %/plant. From two factors then obtained 16 combined treatment with 3 replications. Parameters measured were increase of seed high, increase of midrib number, increase of hump circumference, root volume, root crown ratio and dry seeds weight. The data were analyzed using ANOVA followed by Duncans further test at 5% level. The results of the research showed that application sludge and cow urine on oil palm seed there is interaction between giving of sludge and cow urine on increase of seed high and increase of hump circumference. Combination treatment of sludge dose with 150 g/plant and cow urine concentration of 60 %/plant showed the best results of all observed parameters. Keywords: Sludge, cow urine, oil palm, main nursery